Analisis Laju Korosi Pada Rantai Jangkar Dengan Variasi Salinitas Air Laut - Almer Mohammed Zuhair Tedjakusumah (2023)
Damage to anchor chains is usually caused by the environment from the sea so that it experiences fatigue due to being exposed to dynamic loads that occur periodically for a long period of time. The purpose of this thesis is to analyze the corrosion rate of the anchor chain against salinity variations experimentally by using Weight Loss Method. Research data collection is carried out using quantitative methods, namely data that can be measured, given numerical values, and calculated. The surface area of each chain has a more significant influence on corrosion rate than salinity on corrosion rate. The salinity of seawater has a role in influencing the corrosion rate although it is not significant. The average corrosion rate of the small chains is 0.626 mm/year. The average corrosion rate of the large chains is 0.0138 mm/year. The surface area of anchor chains has a more significant role to influence the corrosion rate than the salinity of seawater.